‘We’re both here to do a job and that’s all that matters’: Cisgender correctional officer recruit reflections within an unsettled correctional prison culture - Adorjan, Michael (The British journal of criminology, 2021)
Reflecting on new trans prisoner placement policies within Canadian federal prisons, in light of recent changes instigated under the Canadian Liberal Trudeau government, we provide knowledge from cisgender correctional officer (CO) recruits regarding these policy changes and underscore their views of working with officers who identify as transgender. Canada’s new policies recognize the presence of trans prisoners and create new protocols accordingly, simultaneously challenging some of the foundational tenets of the carceral system. While overwhelming support exists from cisgender recruits for their trans colleagues, support among a relative minority of COs is contingent upon notions like safety and security grounded in a dominantly cisgender prison culture; a culture we situate within the wider context of an unsettled correctional prison culture.